Shirking from home?: the effects of remote work on overstatement of working hours - Lima, Myrna Modolon (2022)
This study investigates the effect of remote work and the moderating effect of social norms on workers\' self-reporting behavior regarding working hours. Literature does not have a consensus over the effect of physical distance on the overstatement of working. So, my first research question explores whether remote work affects the overstatement of working hours. Literature also does not have a consensus over the combined effect of remote work and peers social norms on the overstatement of working hours. So, my second research question explores the combined effect of remote work on the overstatement of working hours. Literature also shows that two factors might explain the relationship between remote work and overstatement of working hours: auditing likelihood and social pressure. My first hypotheses states that there is an effect of auditing likelihood on the relationship between remote work and the overstatement of working hours. The second hypotheses states that there is an effect of social pressure on the relationship between remote work and the overstatement of working hours. I use an experimental case scenario where I manipulate physical distance (remote work vs. office) and peers\' social norms (honest vs. dishonest). My results from the first research question show that remote work does not exert any significant effect on participants overstatement of working hours. Additionally, my results from the second research question also show that the combined effect of remote work and social norms does not exert any significant effect on the overstatement of working hours. Next, I conduct a mediation analysis to investigate my hypotheses. I find significant effects of the mediating variables on overstatement of working hours: auditing likelihood and social pressure. First, my results show a mediating effect of auditing likelihood on remote workers\' overstatement of working hours, but they do not show the same significant effect for office workers. I attribute this to the role of peers\' information that could display a higher perception of monitoring to remote workers, which is corroborated by recent literature on remote work. Second, my results also show a mediating effect of social pressure on office workers\' overstatement of working hours, but they do not show the same significant effect for remote workers. I attribute these results to the company\'s incentive to work extra hours, acting as a complementary social norm to peers\' social norms for office workers. These results are corroborated by the significant difference between remote workers\' and office workers\' identification with peers and belongingness perceptions, which are crucial aspects of social norms. My results point to different perceptions from remote workers and office workers regarding the company\'s display of information. While remote workers focus on peers\' social norms information as a possible warning from the company and significantly reduce their overstatement of working hours, office workers are significantly affected by the complementary effects between peers\' social norms and the company\'s social norms and significantly increase their overstatement. My results suggest that a company\'s information and social pressure are interpreted differently accordingly to physical distance. Moreover, results from my study can increase companies understanding of the differences between remote workers and office workers self-reporting behavior and the role of the companys information and social pressure on the issue. Specifically for remote workers, companies can focus on targeted information to hinder the overstatement of working hours, given that, for office workers, incentives to overstate hours surpass the risks of opportunistic behavior. Additionally, due to the results on the role of identification with peers and belongingness to the group to the influence of peers social norms, companies can plan their control systems relying on the expected interaction that remote workers will have with peers.